Analytic modelling and optimization of slip synchronous permanent magnet wind turbine generator topologies. (1st May 2014) - Stander, Johan N.; Kamper, Maarten J.; Venter, Gerhard
Abstract The modular slip‐synchronous permanent magnet generator (SSPMG) is viewed as an induction‐synchronous machine pair that is electromagnetically decoupled by a free‐rotating rotor that in turn houses two different sets of permanent magnets. This machine pair combines the advantages of both conventional induction and permanent magnet synchronous machines. It therefore has the potential to realize a new path in reliable, robust and cost‐effective wind turbine drivetrains. However, which electromagnetic SSPMG topology is best and how does it compare with conventional drivetrain designs for various capacities? To date, the most published SSPMG advances are specific to winding design, torque quality and performance optimization in the small capacity range. This paper presents optimized analytic electrical designs of modular, radially and axially separable, radial flux SSPMG topologies of capacities ranging from 100 kW to 5 MW. Designs are based on lumped analytic models and are optimized for minimum specific active mass (mass/torque). A rated efficiency of 95 % and an inductive power factor of 0.95 are applied to all designs. The analytic models are validated with transient two‐dimensional finite element analysis results. The best SSPMG topologies are determined and compared with conventional drivetrain designs. The axially separable topology seems to be the best SSPMG design. Copyright © 2014 John Wiley & Sons, Ltd.